Factors influencing adult carer support planning for unpaid caregiving at the end of life in Scotland: Qualitative insights from triangulated interviews and focus groups. (24th August 2021) - Swan, Susan; Meade, Richard; Cavers, Debbie; Kimbell, Barbara; Lloyd, Anna; Carduff, Emma
Abstract: Caring for a relative or friend at the end of life can be rewarding but all‐encompassing. These caregivers are often not identified, meaning their diverse needs remain unmet, and the lack of assessment, support and planning increases the likelihood of crisis and burnout. The Carers (Scotland) Act 2016 places responsibility on local authorities to implement such a plan, which will be fast‐tracked for carers supporting someone at the end of life. Our research described the factors which might influence this planning, triangulating primary focus groups with 15 carers and secondary qualitative data from transcripts with 30 carers, all of whom who had looked after someone with a terminal illness. Analysis was iterative, and constant comparative analysis of the secondary data informed the primary focus groups. Three main themes were identified; 1. The importance of early identification as a carer to enable timely assessment and support. 2. Carers experience isolation and loneliness which limits opportunities for support. 3. Responding in a timely fashion to carer assessment and support is vital to avoid crises. This research confirms that identifying carers early in the illness trajectory, ideally at diagnosis, is vital to avoid carer burnout. Health and social care providers have a key role in identification and should ensure, where possible, that carer needs are dynamically assessed, supported and documented. Finally, caring does not end after death, it extends into bereavement. Thus, we need to consider system and cultural change to ensure the experiences and needs of carers are addressed and valued.